Tele-kiss. Nam-June Paik’s expanded media in the light of Zen Buddhism - Lipiński, Kamil (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The article offers a broad overview of Nam-June Paik’s ideas of the expansion of video arts interpreted in the light of Zen Buddhism. His works recognized as the most significant examples of his marriage between the art theory and practice are marked by a thought-provoking vision of participatory culture, communicated in-between the networks in the post-industrial society. Our purpose is to reexamine his attitude to TV culture in the oscillation between Western and Eastern gaze considered in connection to the problems of emptiness and meditation drawn from Zen religious beliefs. In discussing his installations there is special stress to reconstruct his inner-insight into the subject of seeing and watching inscribed in a closed-circuit of the communication network.